Kinetic analysis of bioorthogonal reaction mechanisms using Raman microscopy. (18th September 2019) - Tipping, William J.; Lee, Martin; Brunton, Valerie G.; Lloyd-Jones, Guy C.; Hulme, Alison N.
Abstract : Kinetic analysis of CuAAC and Glaser–Hay bioorthogonal reactions can be achieved with Raman microscopy using alkyne vibrations in the cell-silent region. Abstract : Raman spectroscopy is well-suited to the study of bioorthogonal reaction processes because it is a non-destructive technique, which employs relatively low energy laser irradiation, and water is only very weakly scattered in the Raman spectrum enabling live cell imaging. In addition, Raman spectroscopy allows species-specific label-free visualisation; chemical contrast may be achieved when imaging a cell in its native environment without fixatives or stains. Combined with the rapid advances in the field of Raman imaging over the last decade, particularly in stimulated Raman spectroscopy (SRS), this technique has the potential to revolutionise our mechanistic understanding of the biochemical and medicinal chemistry applications of bioorthogonal reactions. Current approaches to the kinetic analysis of bioorthogonal reactions (including heat flow calorimetry, UV-vis spectroscopy, fluorescence, IR, NMR and MS) have a number of practical shortcomings for intracellular applications. We highlight the advantages offered by Raman microscopy for reaction analysis in the context of both established and emerging bioorthogonal reactions, including the copper(i ) catalysed azide–alkyne cycloaddition (CuAAC) click reaction and Glaser–Hay coupling.